Pengujian High Availability pada Asynchronous DNS Berbasis Restknot menggunakan Algoritma Round Robin - Pratama, I Putu Agus Eka; Andreyana, Putu Veda; Nurjana, Putu Ramaditya (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The existence of the Domain Name System (DNS) through the role of the DNS Record, functions to translate domain addresses into IP addresses. High availability is an absolute condition so that the service from the DNS Server is still available and running well. To make this happen, it is necessary to have an asynchronous API on the DNS server and data management on the DNS record. This research designs and implements RESTKnot as an asynchronous API on DNS Server for DNS record management, accompanied by high availability testing using Load Balancing techniques and the Round Robin (RR) algorithm. The test results show that RESTKnot can help the DNS record management process dynamically, where DNS records can be made through the RESTKnot API and RESTKnot CLI, to be sent to the RESTKnot agent and executed by Knot DNS. The test results also show that RESTKnot can realize high availability through a ten-time system access test scenario, where heavy traffic on the first web server can be immediately diverted to the second web server to achieve high availability.